#### Question

Solve the following quadratic equation for x: x^{2} – 2ax – (4b^{2} – a^{2}) = 0

#### Solution

x^{2} – 2ax – (4b^{2} – a^{2}) = 0

⇒ x^{2} + (2b – a)x – (2b + a)x – (4b^{2} – a^{2}) = 0

⇒ x(x + 2b – a) – (2b + a)(x + 2b – a) = 0

⇒ (x + 2b – a)(x – 2b – a) = 0

⇒ (x + 2b – a) = 0, (x – 2b – a) = 0

∴ x = a − 2b, a + 2b

Is there an error in this question or solution?

Solution Solve the following quadratic equation for x: x^2 – 2ax – (4b^2 – a^2) = 0 Concept: Solutions of Quadratic Equations by Factorization.